Global Disease Burden Estimates of Respiratory Syncytial Virus-Associated Acute Respiratory Infection in Older Adults in 2015: A Systematic Review and Meta-Analysis - Shi, Ting; Denouel, Angeline; Tietjen, Anna K; Campbell, Iain; Moran, Emily; Li, Xue; Campbell, Harry; Demont, Clarisse; Nyawanda, Bryan O; Chu, Helen Y; Stoszek, Sonia K; Krishnan, Anand; et al. (The Journal of infectious diseases, 2020)
Respiratory syncytial virus-associated acute respiratory infection (RSV-ARI) constitutes a substantial disease burden in older adults aged ≥65 years. We aimed to identify all studies worldwide investigating the disease burden of RSV-ARI in this population. We estimated the community incidence, hospitalization rate, and in-hospital case-fatality ratio (hCFR) of RSV-ARI in older adults, stratified by industrialized and developing regions, using data from a systematic review of studies published between January 1996 and April 2018 and 8 unpublished population-based studies. We applied these rate estimates to population estimates for 2015 to calculate the global and regional burdens in older adults with RSV-ARI in the community and in hospitals for that year. We estimated the number of in-hospital deaths due to RSV-ARI by combining hCFR data with hospital admission estimates from hospital-based studies. In 2015, there were about 1.5 million episodes (95% confidence interval [CI], .3 million-6.9 million) of RSV-ARI in older adults in industrialized countries (data for developing countries were missing), and of these, approximately 14.5% (214 000 episodes; 95% CI, 100 000-459 000) were admitted to hospitals. The global number of hospital admissions for RSV-ARI in older adults was estimated at 336 000 hospitalizations (uncertainty range [UR], 186 000-614 000). We further estimated about 14 000 in-hospital deaths (UR, 5000-50 000) related to RSV-ARI globally. The hospital admission rate and hCFR were higher for those aged ≥65 years than for those aged 50-64 years. The disease burden of RSV-ARI among older adults is substantial, with limited data from developing countries. Appropriate prevention and management strategies are needed to reduce this burden.